Photonic sensing : principles and applications for safety and security monitoring - Xiao, George; Bock, Wojtek J. (Hoboken, NJ : Wiley, 2012)
"The impact of certain worldwide threats such as terrorism and climate change can be significantly mitigated by the presence of effective early-detection and early-warning systems. Photonics (the use of light) has the potential to provide highly effective solutions tailored to meet a broad range of specific sensing requirements. This book provides a comprehensive review by leading experts of a wide array of photonic sensors with applications to health, environment, and security. It serves as an invaluable source for engineers, researchers, and technical staff working in the field of photonic sensing, as well as safety and security monitoring"--
"The text comprises a series of commissioned chapters from leading experts in the field of photonic sensing, with the target applications to safety and security"--
Includes bibliographical references and index.
Print version record.
Keywords: Optical fiber detectors; Optical fiber detectors -- Safety measures; Optical fiber detectors -- Security measures; Optical fiber detectors; Optical fiber detectors -- Safety measures; Optical fiber detectors -- Security measures; TECHNOLOGY & ENGINEERING -- Remote Sensing & Geographic Information Systems; TECHNOLOGY & ENGINEERING -- Sensors; Optical fiber detectors; Optical fiber detectors / Safety measures; Optical fiber detectors / Security measures; Electronic books; Electronic books